2020
DOI: 10.1016/j.visres.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Interocular suppressive interactions in amblyopia depend on spatial frequency

Abstract: In amblyopia, there is an interocular suppressive imbalance that results in the fixing eye dominating perception. In this study, we aimed to determine whether these suppressive interactions were narrowband and tuned for spatial frequency or broadband and independent of spatial frequency.We measured the contrast sensitivity and masking functions of fifteen amblyopic subjects and seventeen control subjects using the quick Contrast Sensitivity Function (qCSF) approach (Lesmes, Lu, Baek, & Albright, 2010). We firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
31
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 44 publications
5
31
3
Order By: Relevance
“…Thus, stimulation of the nontested eye, with identical background delivered to the tested eye, should modulate the monocular sensitivity of the tested eye, which was captured in the ratio termed DSD. The present data agree with previous reports, 35,55 as dichoptic condition indeed changed contrast sensitivity. The extent of the DSD was more or less pronounced based on binocular status: the data showed small but significant DSD in both eyes of stereonormal subjects, while a large DSD was evident in the amblyopic eye of foveally fixating, stereoanomalous amblyopic patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, stimulation of the nontested eye, with identical background delivered to the tested eye, should modulate the monocular sensitivity of the tested eye, which was captured in the ratio termed DSD. The present data agree with previous reports, 35,55 as dichoptic condition indeed changed contrast sensitivity. The extent of the DSD was more or less pronounced based on binocular status: the data showed small but significant DSD in both eyes of stereonormal subjects, while a large DSD was evident in the amblyopic eye of foveally fixating, stereoanomalous amblyopic patients.…”
Section: Discussionsupporting
confidence: 94%
“…We hypothesize that amblyopic inputs do not provide enough suppressive modulation to the dominant eye as observed in subjects with normal binocular vision between nondominant and dominant eyes. These results are backed by a recent article published by Beylerian et al, 55 who have conducted a similar experiment with both monocular contrast sensitivity measurement and a dichoptic condition with a noise mask presented to the contralateral eye, called dichoptic masking, which is similar to our noise background seen by the contralateral eye. They showed that dichoptic masking asymmetrically influenced the amblyopic and the nonamblyopic eyes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…15,16 Several theoretical models of binocular interactions in amblyopia, for example the two-stage model, 17 multiple-pathway contrast gain control model, 18 and contrast gain control and gain enhancement model, 19 suggest that a disruption to the normally balanced dichoptic inhibitory circuits could provide the basis for understanding suppression in amblyopia. In this case a detailed study of dichoptic masking, which is thought to reflect these inhibitory interocular interactions, has been considered a potentially useful avenue to better understand the phenomenon that under conditions of binocular viewing, information from the amblyopic eye is suppressed [20][21][22][23] at an early stage in the visual cortex. 24 Using the dichoptic masking approach, Zhou et al 23 recently observed less suppression from the amblyopic eye to the fellow eye and a normal suppression from the fellow eye to the amblyopic eye in amblyopic adult patients, resulting in a net suppression of the amblyopic eye under binocular viewing.…”
mentioning
confidence: 99%
“…To answer this question, we adopted a dichoptic masking paradigm based on our previous studies. 21,23 In contrast to the studies by Levi et al 40 and Harrad and Hess 22 and Gao et al, 39 we used different combinations of target and masks orientations rather than a fixed target orientation with varied mask orientation. We measured subjects' contrast sensitivity for detecting the target in isolation or under various masking conditions for each eye.…”
mentioning
confidence: 99%